Study on the vasodilatory activity of lotus leaf extract and its representative substance nuciferine on thoracic aorta in rats - Deng, Hao; Xu, Qian; Sang, Xiao-Tong; Huang, Xing; Jin, Li-Li; Chen, Fen-Er; Shen, Qing-Kun; Quan, Zhe-Shan; Cao, Li-Hua (Frontiers in Pharmacology, 2022)
Lotus (Nelumbo nucifera) leaves are widely used for both edible and medicinal applications. For its further utilization, we studied the vasodilatory activity of lotus leaf extract for the first time. In this study, we obtained the extracts using different ratios of water and ethanol, which was followed by polarity-dependent extraction. We found that the CH2Cl2 layer exhibited better vasodilatory activity (EC50 = 1.21 ± 0.10 μg/mL). HPLC and ESI-HRMS analysis of the CH2Cl2 layer using the standard product as a control revealed that nuciferine (Emax = 97.95 ± 0.76%, EC50 = 0.36 ± 0.02 μM) was the main component in this layer. Further research revealed that nuciferine exerts a multi-target synergistic effect to promote vasodilation, via the NO signaling pathway, K+ channel, Ca2+ channel, intracellular Ca2+ release, α and β receptors, etc. Nuciferine exhibits good vasodilatory activity, and it exhibits the potential to be utilized as a lead compound.